Evaluation of a Novel Simulation Curriculum With the Segmented Model in Pediatric Cardiovascular Education - Yang, Ying; Tang, Lan-Fang; Hua, Chun-Zhen; Mao, Jian-Hua; Hong, Yun-Xia (Frontiers in Public Health, 2022)
Objective The need to develop the full range of knowledge, skills, and professionalism poses new challenges for pediatric cardiovascular education. This study aimed to investigate the effectiveness of a novel simulation curriculum with the segmented model for pediatric cardiovascular residents. Materials and Methods First, the simulation course was designed according to a prior survey and based on a human patient simulator setting. Then, another 55 residents were randomly selected and assigned to participate in a simulation course (about acute fulminant myocarditis in children), either in the experimental group or the control group. Taking full advantage of the simulation education, the simulation case in the experimental group was divided into three segments and included a micro-debriefing at the end of each segment. The three segments were independent but together formed the whole case. It was designed through three cycles of running and debriefing, and more challenging tasks were gradually proposed to residents. The case in the control group was not split and included only one case running and debriefing. The assessments of the residents' knowledge, skills, professionalism performance, and satisfaction feedback from residents were analyzed to evaluate the effectiveness of the course. Results In total, 44 residents completed the whole experimental period, including 23 participants in the experimental group and 21 participants in the control group. The pre-course knowledge assessment scores of the two groups were comparable, while the mean post-course score in the experimental group was 82.61 ± 17.38, which was significantly higher than that in the control group (50.48 ± 18.57, p < 0.01). The mean skills assessment score of residents in the experimental group was 84.17 ± 6.01, which was significantly higher than the control group (54.50 ± 5.72, p < 0.01). In terms of the professionalism assessment, the residents in the experimental group achieved better performance than those in the control group in all aspects (respect, privacy, communication, responsibility, and cooperation) (p < 0.05). Satisfaction feedback from residents showed that self-confidence regarding knowledge mastery in the experimental group was significantly higher than that in the control group (p < 0.05), while there were no significant differences in the evaluations of the teacher's performance (p > 0.05). Conclusions The novel simulation curriculum with the segmented model helps residents achieve better performance in terms of knowledge, skills, and professionalism while improving self-confidence. It has some value in pediatric cardiovascular education and is worthy of further promotion.